Screening of cold hardiness-related indexes and establishment of a comprehensive evaluation method for grapevines (V. vinifera) - Wang, Zhi-Lei; Wu, Dong; Hui, Miao; Wang, Ying; Han, Xing; Yao, Fei; Cao, Xiao; Li, Yi-Han; Li, Hua; Wang, Hua (Frontiers in Plant Science, 2022)
The goals of this work were to screen physiological and biochemical indexes to assess a set of V. vinifera germplasm resources, to compare evaluation methods for cold resistance, and to establish a comprehensive method that can be used for more accurate screening for cold resistance in V. vinifera. Four single methods were used to evaluate the cold resistance of 20 germplasms resources and 18 physiological and biochemical indexes related to cold resistance were determined. The LT50 values determined by electrical conductivity (EL), 2,3,5-triphenyltetrazolium chloride staining (TTC), differential thermal analysis (DTA), and recovery growth (RG) methods showed extremely significant positive correlation. Bound water content (BW), proline content (Pro), total soluble sugar content (TSS), malondialdehyde content (MDA), catalase content (CAT), and ascorbic acid content (ASA) exhibited significant correlation with LT50 values measured by different evaluation methods. The comprehensive cold resistance index calculated by principal component analysis (PCA) combined with subordinate function (SF) was negatively correlated with LT50 values measured by different evaluation methods. Meili and Ecolly exhibited the highest cold resistance, indicating their potential for use as parents for cold resistance breeding. EL, DTA, TTC, and RG methods successfully distinguished cold resistance among different V. vinifera germplasm lines. Measurements of BW, Pro, TSS, MDA, CAT, and ASA in dormant branches also can be used as main physiological and biochemical indexes related to cold resistance of V. vinifera. Comprehensive evaluation by PCA combined with SF can accurately screen cold resistance in V. vinifera.